Kunvarji Group - Roy, Debjit, (SAGE Knowledge. Cases., 2015)
Kunvarji Group, a market leader in the commodity trading and financial services business led by Nayan Kunvarji, Chairman and Managing Director and Chetan Kunvarji, Managing Director. The group, in 2013, envisioned transforming the commodity trading business into the service-driven business. Though it had already started to transform it by diversifying into financial services and real estate, the volatility in capital market and market trend was a bottleneck to the group's profit margin. Further, a large number of commodity traders had entered in the business and commodity producers were also becoming price concerned.